PREVENTION OF CORRUPTION CRIMES THROUGH THE CORRUPTION-FREE AREA INTEGRITY ZONE PROGRAM AT STATE OFFICES AND INSTITUTIONS - Kadir, Abdul; Fitri Ida Laela (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
Written between The increase in corruption cases that occurred in Indonesia released by Transparency International Indonesia (TII) increased the achievement of scores on the Corruption Perception Index (CPI). Although the increase is not significant, corruption is an extraordinary crime. The commitment to realizing corruption prevention are through an Integrity Zone (ZI) development in an integrated and planned corruption-free area. This study aims to analyze the prevention of criminal acts of corruption through the ZI corruption-free area program in state offices and institutions. 1. How is the implementation of corruption-free area integrity zones in state offices and institutions in preventing corruption in Indonesia? 2. What are the obstacles to the implementation of the corruption-free area integrity zone program in preventing corruption in state offices and institutions? This study uses normative research methods. The results of the study can be concluded that in the implementation of integrity zones towards corruption-free areas two types of components must be built in predetermined work units, namely lever components and outcome components where each component is interconnected and component development indicators through ZI Design, Development ZI, Proposal, Review, Determination. Corrupt actions will not just disappear without awareness of the moral behavior itself within the authority, power, and position it holds as an integrity pact. Integrity pact as a commitment must be carried out consistently and the need for maximum socialization is known to the general public so that the community can participate in implementing the ZI development program and not only limited to disseminating related information only to designated agencies/units.